Peran Intervensi Gizi Spesifik Dalam Penanggulangan Masalah Gizi Pada Balita di Kabupaten Bulukumba - Kurniati Akhfar; Erniawati Erniawati; Bau Kanang; Husnul Khatimah; Jusni Jusni (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia is still facing major challenges in the field of nutrition. Lack of nutritional intake is a type of nutritional problem that can cause disturbances in the growth and development of children, so efforts are needed to be made to overcome them. Specific nutrition interventions have been shown to reduce nutritional problems through supplementation and fortification interventions, supporting exclusive breastfeeding, counseling about children's diets, and providing additional food. This study aims to identify specific interventions that have been carried out in addressing under-five nutritional problems using qualitative methods using non-probability sampling techniques. Data was collected through in-depth interviews. The results showed specific nutrition interventions, namely toddler interventions (monitoring toddlers at posyandu, immunization, vitamin A, and PMT). Maternal intervention (pregnancy women's classes, PMT for pregnant women, nutrition and health seminars) and youth interventions (blood-boosting tablets/TTD program).